DEVELOPMENT OF RELEVANT AND INTERESTING ENGLISH TEACHING MATERIALS FOR ELEMENTARY SCHOOL STUDENTS - Al-Faj'rii, Nurul Hasana Lail; Korompot, Chairil Anwar; Sally, Fauzan Hari Sudding (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to identify relevant and interesting English teaching materials for elementary school students and analyze their impact on students' motivation and learning outcomes. This study employs a qualitative and quantitative method (mixed method) with participants consisting of the fifth-grade students at SDN 2 Sawerigadi. The data were collected through observations, interviews, and questionnaires and were analyzed descriptively. The findings indicate that the use of relevant and interesting teaching materials positively contributes to students' motivation in learning. The implemented strategies of developing teaching materials include the use of visual media, interactive learning methods, the selection of themes relevant to students' daily lives, and the adaptation to different learning styles (visual, auditory, kinesthetic). The positive impact is evident in the increase in students' learning motivation, as reflected in their active participation in class and improved learning outcomes. Questionnaire data show that after using the developed teaching materials, most students experienced better comprehension and academic progress. Therefore, it can be concluded that relevant and interesting teaching materials can enhance elementary school students' motivation and learning outcomes in English language learning.